History Education and (Post-)Colonialism International Case Studies - Popp, Susanne; Gorbahn, Katja; Grindel, Susanne (Peter Lang International Academic Publishers, 2019)
This book deals with the challenges for history education arising from the centrality of colonialism in shaping the modern world. It breaks new ground by bringing together an international range of national studies on the legacies of colonialism that permeate the way how colonial history is thought and taught at schools. The case studies examine the representation, understanding and use of colonial heritage from different angles: They focus on European and non-European states as well as on states with and without colonial past as colonizers or colonized. Thus, and with its wide range of approaches - postcolonial theory, memory studies, educational media studies, teaching practice - this volume makes an essential research contribution to the ongoing international debate on the position of colonial history in present and future history education.